2023
DOI: 10.1037/cns0000263
|View full text |Cite
|
Sign up to set email alerts
|

Mind wandering, motivation, and task performance over time: Evidence that motivation insulates people from the negative effects of mind wandering.

Abstract: In the current study, we examined whether participant motivation was associated with fluctuations of attentional engagement and performance over time. We gauged participants' motivation and depth of mind wandering as they completed the metronome response task to determine whether fluctuations in inattention (indexed by task performance and depth of mind wandering) would be related to fluctuations in motivation. As in prior work, we found that, with increasing time on task, (a) self-reported depth of mind wande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Specifically, studies that measured mind wandering during cognitive tasks (e.g. working memory tasks) have shown that mind wandering increases with increased time-on-task (Brosowsky et al 2020;Krimsky et al 2017;Thomson et al 2014). To explain this finding, Browosky et al (2020) suggested that at the start of a cognitive task-which is often new to participants-people allocate relatively high on-task focus, since they are then still lacking sufficient knowledge on the task's costs and benefits (see also Kurzban et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies that measured mind wandering during cognitive tasks (e.g. working memory tasks) have shown that mind wandering increases with increased time-on-task (Brosowsky et al 2020;Krimsky et al 2017;Thomson et al 2014). To explain this finding, Browosky et al (2020) suggested that at the start of a cognitive task-which is often new to participants-people allocate relatively high on-task focus, since they are then still lacking sufficient knowledge on the task's costs and benefits (see also Kurzban et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies (Brosowsky et al, 2020;Thomson et al, 2014), we expected that mind wandering rates would increase (H3a) and tracking performance would decrease over time (H3b). However, we found that mind wandering rates increased only from the first to the second block, remaining stable from the second block onwards, indicating that there were ceiling effects for the amount of time spent mind wandering during this task.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be that learning would take place if this task was performed across various days as in Boyd and Winstein (2004) and Boyd and Linsdell (2009). In addition, due to the task's length (and the fact that participants were aware that they would be performing such a repetitive task for about an hour), it is likely that participants quickly became less motivated to focus on the task, and engaged in mind wandering instead (Brosowsky et al, 2020;Thomson et al, 2014), which in turn, led to no improvements in tracking performance. Recently, Brosowsky et al (2020) found that increased levels of motivation mitigate declines in performance caused by mind wandering as time on task increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probed TUT-report rates appear to be valid individual-differences measures, as they are reliable across different tasks and occasions (e.g., Kane et al, 2016;Unsworth et al, 2020) and they correlate with other measures argued to reflect mind wandering and attentional lapses, such as RT variability (Bastian & Sackur, 2013;McVay & Kane, 2012;Seli et al, 2013b;Unsworth et al, 2010), pupil dilation and eye movements (Reichle et al, 2010;Zhang et al 2020), and retrospective self-reports of mind wandering propensity (Carriere et al, 2013;Mrazek et al 2013;Seli et al, 2016a. Variation in TUT rate is also predicted by measures of theoretically relevant constructs like working memory capacity (WMC) and attention-control ability (McVay & Kane, 2012;Kane et al, 2016;Rummel & Boywitt, "Goldilocks Zone" for Thought Probes 4 2014; Robison & Unsworth, 2018), Attention-Deficit/Hyperactivity Disorder symptoms (Franklin et al, 2017;Seli et al, 2015b;Meier, 2021), and motivation for and interest in the ongoing activity (Brosowsky et al, 2020;Robison et al, 2020;Seli et al 2015a).…”
Section: For Reliable and Valid Measurementmentioning
confidence: 99%